Diabetes mellitus and Urinary Tract Infection: Spectrum of Uropathogens and their Antibiotic Sensitivity - Acharya, Dhruba; Bogati, B; Shrestha, GT; Gyawali, P (Journal of Manmohan Memorial Institute of Health Sciences, 2015)
The incidence of urinary tract infections (UTIs) is common in both diabetic and non diabetic patients. Since the microorganisms causing UTI vary in their susceptibility to antimicrobials from place to place and time to time, hence constant screening of trends and susceptibility pattern of predominant   organisms against antimicrobials is essential. The study aims to determine the spectrum of  ropathogens and antibiotic sensitivity pattern in both diabetic and non diabetic patients with clinically suspected UTI .A prospective cross sectional study was conducted during period of February 2013 to July 2013 among 90 diabetic and 90 non diabetic patients attending Dhulikhel Hospital-Kathmandu University Hospital,  Dhulikhel, Kavre (DH-KUH). All samples and isolates were investigated by standard laboratory rocedures. A total of 55 (30.5%) samples showed significant growth. No significant difference among culture positivity rate was noted between diabetic and non diabetic patients (34.5% Vs 26.7%). Escherichia coli was the most frequent organism (64.5% in diabetic and 66.7% non diabetic) followed by Klebsiella sps (22.6% in diabetic and 12.5% in non diabetic). Gentamycin and nitrofurantoin were highly sensitive to E. coli isolated in diabetic patients among the tested antimicrobials followed by  otrimoxazole, norfloxacin and ciprofloxacin. Least sensitivity rate was observed with ampicillin and cephalexin. However, no difference was noted on the sensitivity pattern of the antimicrobials among E. coli isolated between diabetic and non diabetic patients. In this study high proportion of gram negative bacilli with predominant uropathogen being E. coli was noted. Irrespective of the status of diabetes, Staphylococcus sps and Pseudomonas sps were not isolated from UTI patients in our study. The isolation of organisms and their resistance pattern was almost similar between diabetic and non diabetic patients.DOI: http://dx.doi.org/10.3126/jmmihs.v1i4.11998Journal of Manmohan Memorial Institute of Health SciencesVol. 1, Issue 4, 2015Page : 24-28